Endothelin-1 level in epithelial lining fluid of patients with acute respiratory distress syndrome - NAKANO, Yasushi; TASAKA, Sadatomo; SAITO, Fumitake; YAMADA, Wakako; SHIRAISHI, Yoshiki; OGAWA, Yuko; KOH, Hidefumi; HASEGAWA, Naoki; FUJISHIMA, Seitaro; HASHIMOTO, Satoru; ISHIZAKA, Akitoshi (Respirology (Carlton, Vic.), 2007)
Background and objectives:  Endothelin‐1 (ET‐1), a potent vasoconstrictor peptide produced by endothelial cells, has been implicated in the dysfunction of various organs. To determine the role of ET‐1 in acute lung injury (ALI) and ARDS, ET‐1 levels were measured in epithelial lining fluid (ELF) and plasma obtained from patients with ALI/ARDS. Methods:  A cross‐sectional study of patients with ALI/ARDS in the intensive care unit of two university hospitals was performed. Patients with ALI/ARDS underwent bronchoscopic microsampling to collect ELF on the day of onset of the disease. Patients who underwent bronchoscopy to examine a small peripheral pulmonary nodule served as controls. Results:  In the 23 patients with ALI/ARDS, the ET‐1 level in ELF was significantly greater than that in plasma (P < 0.001). In contrast, ET‐1 was not detectable in the ELF from six of the seven control subjects. The albumin concentration of ELF, used as a marker of endothelial and epithelial permeability, correlated with the ET‐1 level in ELF (P < 0.001). The oxygenation index (PaO2/FiO2) was also correlated with ET‐1 concentration in ELF (P < 0.001). Conclusion:  In patients with ALI/ARDS, ET‐1 is produced mainly in the lung and is associated not only with pulmonary vasoconstriction but also the development of permeability oedema, leading to the impairment of oxygenation.